Climate change impact on cultivated and wild cacao in Peru and the search of climate change-tolerant genotypes - Ceccarelli, Viviana; Fremout, Tobias; Zavaleta, Diego; Lastra, Sphyros; Correa, Sixto Imán; Arévalo Gardini, Enrique; Rodríguez, Carlos Armando; Cruz Hilacondo, Wilbert; Thomas, Evert (Wiley, 2021)
Aim: